ANALYSIS OF CHANGES IN ACCOUNTING PROFIT AND OPERATIONAL CASH FLOW ON STOCK RETURNS - Alferia Nur Khasanah; Samukri; Susi Susilawati; Arlis Dewi (International Journal Management and Economic, 2023)
This study aims to determine the analysis of changes in accounting profit and changes in operating cash flow on the return of shares listed on the Indonesia Stock Exchange (IDX). The sample selection technique used was the purposive sampling method, obtaining a sample of 18 companies with 5 years of observation from 2017-2021, so that the total results of the observation data were 90 data. The data analysis method used is descriptive statistics, panel data estimation model selection, model suitability test, classic assumption test, panel data regression analysis and hypothesis testing using Eviews software version 12. Based on the results of the study partially, it shows that changes in accounting profit have no significant effect on stock returns and changes in operating cash flow have no significant effect on stock returns.